Genome-wide identification and analyses of the AHL gene family in cotton (Gossypium) - Lanjie Zhao; Youjun Lü; Wei Chen; Jinbo Yao; Yan Li; Qiulin Li; Jingwen Pan; Shengtao Fang; Jie Sun; Yongshan Zhang (BMC Genomics, 2020)
Abstract Background Members of the AT-HOOK MOTIF CONTAINING NUCLEAR LOCALIZED (AHL) family are involved in various plant biological processes via protein-DNA and protein-protein interaction. However, no the systematic identification and analysis of AHL gene family have been reported in cotton. Results To investigate the potential functions of AHLs in cotton, genome-wide identification, expressions and structure analysis of the AHL gene family were performed in this study. 48, 51 and 99 AHL genes were identified from the G.raimondii, G.arboreum and G.hirsutum genome, respectively. Phylogenetic analysis revealed that the AHLs in cotton evolved into 2 clades, Clade-A with 4–5 introns and Clade-B with intronless (excluding AHL20–2). Based on the composition of the AT-hook motif(s) and PPC/DUF 296 domain, AHL proteins were classified into three types (Type-I/−II/−III), with Type-I AHLs forming Clade-B, and the other two types together diversifying in Clade-A. The detection of synteny and collinearity showed that the AHLs expanded with the specific WGD in cotton, and the sequence structure of AHL20–2 showed the tendency of increasing intron in three different Gossypium spp. The ratios of non-synonymous (Ka) and synonymous (Ks) substitution rates of orthologous gene pairs revealed that the AHL genes of G.hirsutum had undergone through various selection pressures, purifying selection mainly in A-subgenome and positive selection mainly in D-subgenome. Examination of their expression patterns showed most of AHLs of Clade-B expressed predominantly in stem, while those of Clade-A in ovules, suggesting that the AHLs within each clade shared similar expression patterns with each other. qRT-PCR analysis further confirmed that some GhAHLs higher expression in stems and ovules. Conclusion In this study, 48, 51 and 99 AHL genes were identified from three cotton genomes respectively. AHLs in cotton were classified into two clades by phylogenetic relationship and three types based on the composition of motif and domain. The AHLs expanded with segmental duplication, not tandem duplication. The expression profiles of GhAHLs revealed abundant differences in expression levels in various tissues and at different stages of ovules development. Our study provided significant insights into the potential functions of AHLs in regulating the growth and development in cotton.